Evaluating the Impact of Renewable Energy Policy Instruments on Capacity Expansion: Insights from the Visegrad Group Countries - Kurmanalina, Aigul; Saiymova, Meiramkul; Bolatova, Botakoz; Orynbassarova, Aizhan; Troyanskaya, Marija; Yerkulova, Gulmira; Saimagambetova, Gaukhar (International Journal of Energy Economics and Policy, 2024)
Renewable energy technologies have reached a pivotal point, demonstrating cost competitiveness with traditional energy sources and a continuing trend of affordability. Nevertheless, the successful deployment of renewable energy capacity crucially depends on the efficacy of renewable energy policy tools, casting a veil of uncertainty over their actual influence on the expansion of renewable electricity generation. This research delves into the array of policy instruments designed to bolster renewable energy capacity. Employing an econometric analysis, this study meticulously examines these policy tools, with a particular emphasis on feed-in tariffs, quotas, tenders, and tax incentives, seeking to facilitate the adoption of renewable energy within the Visegrad group countries, comprising the Czech Republic, Hungary, Poland, and Slovakia. Drawing from a comprehensive panel dataset spanning the years from 1990 to 2020, our findings unveil a nuanced perspective on the effectiveness of these renewable energy policy tools. Notably, our results underscore the varying degrees of success among different policy instruments, all of which significantly contribute to the advancement of renewable energy sources. A key revelation arises from the limited impact of quotas, a frequently employed regulatory measure, in stimulating the expansion of renewable electricity generation capacity. In contrast, feed-in tariffs, tenders, and tax incentives emerge as potent drivers in achieving this pivotal objective. This research sheds light on the dynamic landscape of renewable energy policy instruments, offering valuable insights for policymakers and stakeholders engaged in advancing sustainable and resilient energy ecosystems in the Visegrad group countries and beyond.